Pelatihan Analisis Sistem Rekrutmen Digital di Radio Republik Indonesia (RRI) - Handayani, Eka; Pembuain, Fince; Prambodo, Yoga Listi (Publikasi Pengabdian Masyarakat Komputer dan Teknologi (PUNDIMASKOT), 2025)
This training aims to enhance the effectiveness and efficiency of the recruitment process at Radio Republik Indonesia (RRI) through the analysis of a digital-based recruitment system, with a primary focus on workflow mapping using Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD) as the foundation for modern information system design. The training adopts a systematic analysis approach based on information technology to provide a comprehensive understanding of the importance of digital transformation in improving the accuracy, speed, and transparency of recruitment. Through this activity, participants are equipped not only with theoretical knowledge but also with practical skills to analyze manual systems, identify weaknesses, and design more structured and integrated system models. The results of the training indicate a significant improvement in participants' abilities to develop DFDs and ERDs according to information system development standards, thereby strengthening the readiness for implementing a more effective and accountable digital recruitment system. This digitalization is expected to accelerate the selection process, reduce administrative errors, enhance public trust in the integrity of the recruitment process, and promote the creation of an adaptive and responsive human resource management system in the digital era. The improvement of technological literacy within RRI through this training forms a crucial foundation for the successful, sustainable transformation of the organization.